Designing Supplementary Controller With Thyristor-Controlled Series Capacitor for Enhancing Inertia-Sharing Capability - Thongchart Kerdphol (IEEE Open Access Journal of Power and Energy)
To address the challenge of inertia deficiency in multi-area power systems, this paper proposes a novel approach to inertia sharing by leveraging supplementary control integrated with thyristor-controlled series capacitors (TCSC). The proposed supplementary power modulation controller (SPMC) dynamically adjusts TCSC reactance based on frequency and tie-line power deviations to facilitate coordinated inertia transfer from well-equipped areas to inertia-deficient regions. Unlike conventional strategies that rely on deploying additional energy storage systems or distributed virtual inertia units, the proposed method utilizes existing transmission infrastructure, thereby reducing implementation complexity and cost. The efficacy of the proposed control strategy is assessed using a benchmark interconnected model configured to reflect practical multi-area dynamics and intertie constraints. Simulation results confirm that the SPMC-based TCSC control improves transient frequency stability, enhances damping, and increases the efficiency of inertia sharing, even under network congestion and delay conditions. These findings highlight the potential of the proposed strategy as a scalable and practical solution for enhancing dynamic performance in renewable-rich, interconnected power grids.